1972
DOI: 10.1126/science.176.4041.1346
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Spectra and Reaction Time in Disorders of Higher Nervous Function

Abstract: Cerebral electrical abnormalities associated with variability of attention and responsivity were sought in individuals with schizophrenia and epilepsy. Experimental and control subjects were given stimulus-response tasks, and average power spectra for brief electroencephalographic epochs preceding responses of short and long latency were compared. Spectra that precede long-latency or erroneous responses resemble the "ramp" configuration of spectra computed from scalp electroencephalograms for 1-second epochs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Tuvo (1958), Prechtl et al (1961), Sellden (1971 and Hutt et al (1977) found no evidence of TCI during discharges variously described as unilateral, focal or localized. An association of increased reaction time with localized increase in low frequency components of EEG power spectra has been demonstrated, however, by Stevens et al (1972), and these 'ramp spectra' in turn were associated with spiking at depth electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Tuvo (1958), Prechtl et al (1961), Sellden (1971 and Hutt et al (1977) found no evidence of TCI during discharges variously described as unilateral, focal or localized. An association of increased reaction time with localized increase in low frequency components of EEG power spectra has been demonstrated, however, by Stevens et al (1972), and these 'ramp spectra' in turn were associated with spiking at depth electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration increased the probability for an IED-induced deficit. 14 , 32 Other determinants may include IED amplitude 18 , 32 and increased EEG power during epileptiform discharges (called ramp configuration of EEG spectrum 33 ). 18 IEDs were, however, variable within EEG recordings.…”
Section: Discussionmentioning
confidence: 99%
“…Kontro/lt: dt:5 Koukkou und Lehmann, 1968;Stevens et al, 1972;Lehmann und Koukkou, 1974;Nunn und Osselton, 1974;Shimizu et al, 1977 (Lynn, 1966).…”
Section: Der Begriffdes Funktionellen Zustandes Desunclassified